Analisis Geologi Teknik Desa Isimu Raya, Kecamatan Tibawa, Kabupaten Gorontalo, Provinsi Gorontalo - Pahrun, Aliim Risky; Zainuri, Ahmad; Kasim, Muh. (Universitas Negeri Gorontalo, 2025)
This research was conducted in Isimu Raya Village to assess the geotechnical conditions of the study area using quantitative field mapping methods and data analysis. The analysis encompassed the characterization of the physical and mechanical properties of soils, as well as rock analysis. The mapping results indicate that the study area comprises packstone limestone, elastic silt soil units, and low-plasticity sandy clay. Based on laboratory testing of soil physical properties, the elastic silt exhibited a liquid limit of 47.86% and plasticity index values of 48.89% and 54.08%. In contrast, the low-plasticity sandy clay showed a liquid limit of 48.61%, a plastic limit of 15.48%, and a plasticity index of 33.13%.